1991
DOI: 10.1111/j.1464-5491.1991.tb01513.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Carbohydrate Metabolism in Association With Glipizide Treatment of Type 2 Diabetes

Abstract: Nineteen patients with Type 2 diabetes were treated with glipizide for 2.5-6 months, and measurements made of metabolic variables before and after glipizide treatment. For purposes of analysis, the glipizide associated decrease in fasting plasma glucose concentration was used to divide patients into 'good' responders (decrease of 4.0 mmol l-1 or more, n = 9) or 'fair' responders (decrease of 3.0 mmol l-1 or less, n = 10). Good responders had a significantly greater fall in their mean (+/- SE) hourly plasma glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
8
2

Year Published

1993
1993
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
2
8
2
Order By: Relevance
“…Based on these findings, it has been suggested that the ability of insulin to stimulate glucose uptake increases after sulfonylurea treatment of patients with N1DDM (1-5). However, we have not been able to provide experimental evidence for this assumption in two previous studies (4,5). Instead, our results indicated that the improvement in glucose uptake after sulfonylurea treatment could be discerned when measured during glucose clamp studies in response to either basal or elevated insulin concentrations, but the incremental increase in glucose uptake when insulin levels were increased during the clamp was similar before and after treatment.…”
contrasting
confidence: 76%
See 3 more Smart Citations
“…Based on these findings, it has been suggested that the ability of insulin to stimulate glucose uptake increases after sulfonylurea treatment of patients with N1DDM (1-5). However, we have not been able to provide experimental evidence for this assumption in two previous studies (4,5). Instead, our results indicated that the improvement in glucose uptake after sulfonylurea treatment could be discerned when measured during glucose clamp studies in response to either basal or elevated insulin concentrations, but the incremental increase in glucose uptake when insulin levels were increased during the clamp was similar before and after treatment.…”
contrasting
confidence: 76%
“…CONCLUSIONS -Results of several published studies have shown that improvement in glycemic control in sulfonylurea-treated patients with NIDDM was associated with enhanced glucose uptake measured during glucose clamp studies (1)(2)(3)(4)(5). Based on these findings, it has been suggested that the ability of insulin to stimulate glucose uptake increases after sulfonylurea treatment of patients with N1DDM (1-5).…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…All of these changes have been previously demonstrated to occur with glipizide treatment of patients with NIDDM [27,28].…”
Section: Discussionmentioning
confidence: 98%